Finance, Budget, and Management for Reference Services, 1st edition - Fraley, Ruth A. (Routledge, 2020)
The library budget, a topic of primary importance to the reference librarian, is thoroughly examined in this book, first published in 1988. Experts offer insightful suggestions for reference librarians to understand and take responsibility for budget issues, directly and indirectly. They address the ability to explain the budget - which actually entails explaining the collection, the services, and the process in place for managing the fiscal resources - a necessary skill for any reference librarian faced with looming budget cuts. Providing quality services on a limited budget is also explored. The contributors provide helpful essays on convincing the parent agency to provide adequate support, setting goals and priorities, generating revenue, and more.